The Language of Business Codes of Ethics: Implications of Knowledge and Power - Farrell, Helen (Journal of business ethics, 1998)
In Australia as is the case elsewhere, ethics is a developing aspect of business behaviour. Many educational institutions and business enterprises have a strong interest in the subject, particularly from the practical viewpoint of creating an ethical culture in business that has substantial practical effects. In this paper, the codes of ethics of five large enterprises are examined. They were selected as being typical of a collection of corporate codes used in Australia held by the Ethics Research Group at the University of Technology, Sydney. Two codes were from international companies: a chemical manufacturing company and a health, beauty and medical manufacturer. The other codes were from an Australian bank, an Australian federal government business agency, and an Australian mining company., Corporate codes of ethics rarely contain operational definitions to direct their addressees on situations of moral hazard and the required response, to achieve a particular desired ethical corporate culture. Consequently, addressees constitute the locus of ethical decision making in enterprises. By contrast, the language used in the corporate codes examined construct an authoritarian position in the writer/reader relationship from the overuse of grammatical structures such as relational clauses, the passive, nominalisation, grammatical metaphor and modality. Collectively, these structures communicate a strong sense of obligation and even powerlessness since a strong authoritarian tone is established which does not give the addressees the possibility of discretionary decision making., The authors acknowledge that these five grammatical structures have a place in corporate codes since they form part of the legitimate linguistic fabric of our language. Rather attention is drawn to this overuse to assist corporate code authors to avoid writing codes that have subtle unintended and contradictory messages.